Knowledge and attitudes of brazilian dentists towards the dental treatment of chronic kidney - Andrade, Natália Silva; Gallottini, Marina (Journal of Oral Diagnosis, 2020)
Chronic kidney disease (CKD) is characterized by metabolic alterations and progressive irreversible loss of the kidney’s ability to perform glomerular filtration. Dental follow- up and handling of individuals with CKD is important and represents a challenge for the dentists. Thus, the aim was to assess the knowledge, attitudes, and practices of Brazilian dentists towards the dental treatment of CKD patients. This research employed a cross-sectional study conducted between June and September 2019, with 488 dentists, from São Paulo, SP, Brazil. Data collection occurred through application of a structured self-report form using Google Forms tool. The questions addressed clinical knowledge towards dental treatment of patients with CKD, during invasive or non-invasive dental procedures. Sociodemographic data were collected by using the same questionnaire. A descriptive analysis of the data, Chi-square and Linear Association tests were performed. A significant percentage of participants (223/488; 45.7%) felt uncomfortable performing invasive dental treatments in CKD patients. The great majority (385/488, 78.9%) would prescribe prophylactic antibiotics before invasive dental procedures, whereas 18.2% would prescribe antibiotics, even before non-invasive procedures. Most dentists recommended this practice to prevent colonization of the venous access for haemodialysis (225/448; 57.4%), and to prevent infective endocarditis (176/488; 44.9%). Female gender (268/385; 69.6%) and private higher education institution (250/385; 64.9%) were found to be associated with the prescription of prophylactic antibiotics in CKD individuals on haemodialysis (p < 0.005). Our results showed that most interviewed dentists prescribe prophylactic antibiotics inadvertently not following the current recommendations of recognized international associations.